Development Of In Vitro Regeneration System For Capsicum Annuum And Transformation With Cucumber Mosaic Virus Coat Protein Gene - Pua, Teen Lee (2007)

(untitled)
Chilli is one of the most important crops grown worldwide. It ranks as the most popular fruit vegetable and occupies the highest hectarage among the fruit vegetables in Malaysia. However, like any other crop of economic importance, chilli production is hampered by various virus diseases, especially Cucumber Mosaic Virus (CMV) disease. Genetic engineering seems to be the most important technique for the development of novel chilli cultivars with virus resistant property, since other conventional controls were highly ineffective. This study was carried out in three stages: first, to establish an efficient in vitro regeneration system for a local chilli cultivar Cilibangi-4 (CB4); second, to obtain a transforming vector containing Cucumber Mosaic Virus (CMV) Coat Protein (CP) gene; and third, development of transgenic chilli plants with CMV resistant. The investigation was initiated to study the in vitro regenerative ability of seven local chilli cultivars (Capsicum annum cv. CB2, CB3, CB4, CB6, MC11, MC12 and Kulai) and to select the most responsive cultivar for subsequent experiments. Explants (hypocotyls and cotyledonary leaves) were collected from 10-12 day-old seedlings and subjected to differentiation medium (DM). Genotypic differences for the in vitro regeneration ability were observed in this study. Of all the genotypes tested, cultivar CB4 was found to be the most responsive for both hypocotyls and cotyledonary leaves tested. Hence, subsequent experiments were carried out by using CB4. BA and IAA concentrations have been optimised for DM. Five concentrations of both PGRs were tested, 5 mg/l(w/v) BA and 0.5 mg/l(w/v) IAA were only found to be the most suitable for bud induction. Up to 87.5% of the cultured hypocotyls formed buds in the induction medium and cotyledonary leaves with a lower percentage of 65%. Effects of other cytokinins and auxins were investigated as well for bud induction in DM. Kinetin and zeatin were found to be less effective on bud induction compared to BA. While, Thidiazuron (TDZ) showed an extremely high percentage of bud formation, yet the buds induced were mostly stunted buds due to its high cytokinin activity. For auxins, Phenylacetic acid (PAA) was tested. PAA has shown some encouraging results among the concentrations tested. However, the buds seemed likely to form a rosette of distorted leaves and refused to develop further. Elongation of shoot buds was examined. Treatment DMM (Buds were induced in DM and elongated on MS with 3% sucrose) was found to be the best among all the treatments applied. The leaves formed expanded as normal, shoots elongated well and the roots developed vigorously at the basal part of the explants. Shoots elongated were excised and allowed to root in PGR-free MS medium. A construct of a plant expression cassette with CMV CP gene has been successfully cloned. The cloned CMV CP fragment was 655 bp and exhibited more than 90% similarity to those published CMV CP gene sequences. The effectiveness of kanamycin in selecting transformed tissue has been investigated based on the minimal kanamycin concentration was that capable to thoroughly inhibit and/or kill all the non-transformed tissues. The minimal inhibitory concentrations of kanamycin were 100 and 200 mg/l(w/v) for cotyledonary leaves and hypocotyls, respectively. Agrobacterium tumefaciens strain EHA105 harbouring the CMV CP construct was used to transform the chilli hypocotyls and cotyledonary leaf explants. The putative transformants were screened by subjecting to polymerase chain reaction (PCR) with specific primers. Unfortunately, no positive result was obtained.